Codex alimentarius: Vol.1A: General requirements: Joint FAO/WHO Food Standards Programme Codex Alimentarius Commission - FAO (FAO, 1995)
The Codex Alimentarius ( Latin, meaning Food Law or Code ) is a collection of international food standards adopted by the Commission and presented in a uniform manner. It includes standards for all the principal foods, whether processed or semi-processed or raw. Materials for further processing into foods are included to the extent necessary to achieve the purposes of the Codex Alimentarius as defined. The Codex Alimentarius includes provisions in respect of the hygienic and nutritional quality of food, including microbiological norms, provisions for food additives, pesticide residues, contaminants, labelling and presentations, and methods of analysis and sampling. It also includes provisions of an advisory nature in the form of codes of practice, guidelines and other recommended measures.